描述变胞机构构态变化的改进邻接矩阵 - 卢伍鋆; 蓝兆辉 (Jixie chuandong)
In order to overcome the problem of existing methods on the configuration description of metamorphic mechanisms,a new adjacent matrix,which can describe all kind of conditions,is put forward. The process of topological changes can be described clearly by one adjacent matrix,and complex matrix operations are not needed.